2016
DOI: 10.1101/061598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent Protection Against H5N1 and H7N9 Influenza via Childhood Hemagglutinin Imprinting

Abstract: Two zoonotic influenza A viruses (IAV) of global concern, H5N1 and H7N9, exhibit puzzling differences in age distribution of human cases. Previous explanations cannot fully account for these patterns. We analyze data from all known human cases of H5N1 and H7N9 and show that an individual's first IAV infection confers lifelong protection against severe disease from novel hemagglutinin (HA) subtypes of the same phylogenetic group. Statistical modeling reveals protective HA imprinting to be the crucial explanator… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
147
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(160 citation statements)
references
References 64 publications
6
147
2
5
Order By: Relevance
“…Indeed, there is much evidence that immune responses, and hence risk of infection and disease severity, are heavily influenced by past influenza exposure (8,9). We agree with Shanks and Brundage (2) that exposure to a prior influenza strain is a plausible contributing factor in explaining age-specific mortality during the pandemic.…”
supporting
confidence: 69%
“…Indeed, there is much evidence that immune responses, and hence risk of infection and disease severity, are heavily influenced by past influenza exposure (8,9). We agree with Shanks and Brundage (2) that exposure to a prior influenza strain is a plausible contributing factor in explaining age-specific mortality during the pandemic.…”
supporting
confidence: 69%
“…We sought to identify susceptibility gene(s) which may account for the inter‐individual variability to severe influenza from the GWAS previously conducted in the H7N9 cohort and the pandemic H1N1 cohort. Besides the genetic contribution, emerging evidence suggested that broadly protective immune responses due to the childhood infection can provide long‐term cross‐immunity among different HA subtypes, especially those in the same phylogenetic group (Gostic et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CD8+ T‐cell immunity toward epitopes against internal conserved viral proteins in both mice and ferrets is exaggerated as compared to humans and can provide very solid protection against challenge, something not observed to the same degree in humans. Another limitation of animal models is that humans have long and complex exposure histories to influenza viruses through vaccination and/or infection, including imprinting effects . These complex exposure histories influence the immune responses to subsequent infection and vaccination and cannot be effectively recapitulated in animal models (pre‐exposed ferret models can be used but are very simplified compared to humans) .…”
Section: Correlates Of Protection and Animal Modelsmentioning
confidence: 99%